Manejo de datos de germoplasma - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
In Jan. 1984, a project was initiated at CIAT to improve the management of data for the Bean Program and the Genetic Resources Unit through the use of IDMS/R (Integrated Data Management System, Relational), a system produced by Cullinet Software Inc. The principal advantages of this system for the bean program, over others, are: (a) it handles large amounts of data and (b) full integration between microcomputers and the central database on the mainframe is built into the system. The main objectives for the use of this system are presented. (CIAT)